2017
DOI: 10.1177/2047487317725017
|View full text |Cite
|
Sign up to set email alerts
|

GDF-15 and TRAIL-R2 are powerful predictors of long-term mortality in patients with acute myocardial infarction

Abstract: Background The Proximity Extension Assay proteomics chip provides a large-scale analysis of 92 biomarkers linked to cardiovascular disease or inflammation. We aimed to identify the biomarkers that best predicted long-term all-cause mortality in patients with acute myocardial infarction. Methods In this prospective cohort study, 92 biomarkers were analysed in 847 consecutive patients from the Västmanland Myocardial Infarction Study with a median follow-up of 6.9 years. Results The mean (± standard deviation) ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 33 publications
4
64
0
2
Order By: Relevance
“…Raised circulating TRAIL-R2 levels have been linked with cerebral atherosclerosis [36] and increased mortality in acute myocardial infarction [37]. Possible mechanisms linking the TRAIL/TRAIL-R2 pathway to atherosclerotic disease involve the endothelial response to cholesterol deposits [37, 38] and the composition of circulating fatty acids, as a study in an Alaskan Inuit population found an association between plasma fatty acid levels and genetic variants of the TRAIL-R2 gene TNFRSF10B [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Raised circulating TRAIL-R2 levels have been linked with cerebral atherosclerosis [36] and increased mortality in acute myocardial infarction [37]. Possible mechanisms linking the TRAIL/TRAIL-R2 pathway to atherosclerotic disease involve the endothelial response to cholesterol deposits [37, 38] and the composition of circulating fatty acids, as a study in an Alaskan Inuit population found an association between plasma fatty acid levels and genetic variants of the TRAIL-R2 gene TNFRSF10B [39]. …”
Section: Discussionmentioning
confidence: 99%
“…The TRAILR2 protein (otherwise known as death receptor 5) is encoded by the TNFSF10 gene and is a receptor belonging to the TNF superfamily that preferentially induces apoptosis after binding of its ligand TRAIL 29,30 . Increased levels of TRAILR2 have been associated with adverse cardiovascular events in patients with myocardial infarction, probably due to intensified apoptotic activity 31 . Interleukins, as "upstream" biomarkers of inflammation converge on the central TNF signalling pathway, having major influence on atherosclerosis, and consequently on the risk of cardiovascular disease 32 .…”
Section: Inflammation and Apoptosis Clustermentioning
confidence: 99%
“…The results from previous studies have shown that increased circulating GDF15 levels were closely associated with the development and progression of various cardiovascular diseases (including myocardial ischaemia/reperfusion, heart failure, atherosclerosis, and acute coronary syndrome), and were shown to be a strong and independent predictor of mortality and disease progression in patients with atherosclerosis and coronary artery disease [5][6][7][8][9][10][31][32][33][34][35][36]. In diabetic patients, higher levels of lipids and chronic inflammation may directly damage the cardiovascular system [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, the expression and secretion of GDF15 can be strongly induced in the case of cardiovascular injury, such as pressure overload, myocardial infarction, heart failure, and atherosclerosis [4]. In recent years, a series of clinical studies [5][6][7][8][9][10] have reported that high circulating GDF15 levels are an independent predictive factor for several cardiovascular diseases in patients with atherosclerosis and acute coronary syndrome, and that investigating the levels of GDF15 could improve risk prediction beyond traditional risk factors and biochemical indicators.…”
mentioning
confidence: 99%